Efektivitas Pengencer Alternatif Berbasis Air Kelapa Hijau Muda Dan Tua Terhadap Kualitas Semen Cair Sapi Bali Selama Simpan Dingin - Mohamad Ervandi‬; Widiastuti Ardiansyah; Suci Ananda (Universitas Muhammadiyah Gorontalo, 2026)
This study aimed to evaluate the effectiveness of young and mature green coconut water as alternative semen extenders for preserving the quality of chilled Bali bull liquid semen. The experiment was conducted over a three-month period at the Field Laboratory of the Department of Animal Science, Faculty of Science and Computer Science. A laboratory experimental approach was employed. Semen was collected once a week from two healthy Bali bulls aged 2–3 years. Young green coconut water and mature green coconut water (6–7 months of maturity) were used as alternative extenders, while CEP-2 supplemented with 10% egg yolk served as the control. The experiment was arranged in a completely randomized design (CRD) with three treatments: A1 = CEP-2 + 10% egg yolk (control), A2 = young green coconut water + 10% egg yolk, and A3 = mature green coconut water + 10% egg yolk. Each treatment was replicated ten times. The data were analyzed using analysis of variance (ANOVA) with SPSS version 20. The evaluated parameters included individual sperm motility, sperm viability, and sperm abnormalities. The results demonstrated that the highest individual sperm motility was observed in A3 (42.57 ± 2.06%), followed by A2 (41.15 ± 0.49%), with both treatments maintaining acceptable motility for up to four days of chilled storage. The highest sperm viability on Day 5 was also recorded in A3 (42.60 ± 1.71%), followed by A2 (40.50 ± 1.71%). Meanwhile, the lowest sperm abnormality throughout seven days of storage was found in A3 (1.36 ± 0.04%), followed by A2 (1.44 ± 0.10%). These findings indicate that both young and mature green coconut water can serve as effective alternative semen extenders for preserving the quality of chilled Bali bull liquid semen. However, mature green coconut water exhibited superior preservation ability by maintaining sperm motility for up to four days and sperm viability for up to five days during chilled storage. Tujuan penelitian ini mengetahui penggunaan air kelapa hijau muda dan air kepala hijau tua sebagai bahan pengencer terhadap kualitas semen cair sapi bali setelah disimpan. Penelitian ini dilakukan selama 3 bulan, bertempat di Laboratorium Lapang Program Studi Peternakan Fakultas Sains dan Ilmu Komputer. Metode yang digunakan yaitu eksperimental laboratory. Semen yang digunakan berasal dari 2 ekor sapi bali umur 2-3 tahun ditampung 1 minggu sekali. Air kepala hijau muda dan air kepala hijau tua umur 6-7 bulan serta CEP2 sebagai kontrol. Rancangan penelitian menggunakan Rancangan Acak Lengkap (RAL) pola faktorial yang terdiri dari A1 = CEP2 + KT 10% (kontrol); A2 = Air Kelapa Hijau Muda + KT 10% dan A3= Air Kelapa Hijau Tua + KT 10% dan Masing-masing perlakuan dilakukan 10 kali ulangan. Data dianalisis menggunakan Analisis Ragam (ANOVA) dengan bantuan software SPSS 20. Variabel yang di amati adalah motilitas individu, viabilitas dan abnormalitas. Hasil penelitian menunjukkan motilitas individu terbaik pada A3 (42,57 ± 2.06%) disusul A2 (41,15 ± 0.49%) yang bertahan sampai 4 hari simpan, kemudian viabilitas terbaik pada hari ke 5 adalah A3 (42,6 ± 1.71%) disusul A2 (40,5 ± 1.71%), sedangkan abnormalitas terendah sampai hari ke 7 adalah A3 (1,36 ± 0.04%) disusul A2 (1,44 ± 0.10%). Pengencer air kelapa hijau muda dan pengencer air kepala hijau tua dapat mempertahankan kualitas semen cair sapi bali dengan lama simpan selama 4 hari untuk motilitas dan 5 hari untuk viabilitas spermatozoa.